Implementation Application For Measuring Physical Fitness Test Results In Badminton - Praja, Muhammad Dimas; Hartati, Hartati; Aryanti, Silvi (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2024)
The study, titled "Implementation of Physical Fitness Test Measurement for Badminton Players Using Applications for Students at Palembang 04 Public Junior High School," aims to establish norms for assessing physical fitness in badminton through the use of applications. Key components, including endurance, speed, strength, and explosive power, are crucial for volleyball. This quantitative research employs a descriptive research design and involves 30 volleyball extracurricular students from Palembang 04 Public Junior High School, comprising 9 male students and 21 female students. Data collection utilizes various test instruments: T Test Agility for agility, 30-meter running for speed, 1-minute push-ups for arm muscle strength, sit-up test for abdominal muscle strength, and standing board jump test for muscle explosive power. The research is conducted at Palembang 04 Public Junior High School in collaboration with a member of the MGMP Pjok City of Palembang. Results from the study indicate that the average physical condition of badminton extracurricular students at Palembang 04 Public Junior High School falls into the very good category (11.20%), good category (9.40%), fair category (12%), less than average category (40%), and very less than average category (19%). In summary, the overall physical condition of badminton extracurricular students at Palembang 04 Public Junior High School is categorized as poor, accounting for 40%. The intention behind this research is to serve as a discussion point for evaluation, fostering awareness among students to continually improve and maintain their physical fitness for optimal performance.